An Urgent Need for Integration of Family Planning Services Into HIV Care: The High Burden of Unplanned Pregnancy, Termination of Pregnancy, and Limited Contraception Use Among Female Sex Workers in Côte d'Ivoire. (1st March 2015) - Schwartz, Sheree; Papworth, Erin; Thiam-Niangoin, Marguerite; Abo, Kouame; Drame, Fatou; Diouf, Daouda; Bamba, Amara; Ezouatchi, Rebecca; Tety, Josiane; Grover, Elise; Baral, Stefan
Abstract : Background: HIV infection and unintended pregnancy are occupational risks of commercial female sex work (FSW). The burden of unintended pregnancy among FSW including maternal and infant outcomes in the context of HIV is largely unknown. Methods: FSW ≥18 years were recruited through respondent driven sampling into a cross-sectional study in Abidjan, Côte d'Ivoire. Participants completed a sociobehavioral questionnaire and HIV counseling and testing. Pregnancy history by HIV status and contraceptive use were described, and Poisson regression used to estimate correlates of termination of pregnancy (TOP). Results: From March to July 2014, 466 FSW were enrolled. Unintended pregnancy was common, and 64% of participants had ≥1 TOP. Half of FSW experiencing TOPs did so without a medical professional, resulting in frequent complications. Contraceptive use was lowest among younger FSW, and 37% of 20–24 year olds reported multiple TOPs. FSW with a TOP history reported 19% less consistent condom use with clients than women who never had a TOP (adjusted-prevalence ratio, 0.81; 95% confidence interval: 0.74 to 0.88), whereas use of reliable nonbarrier contraceptive methods was comparable between the groups. Although FSW were engaged in HIV testing and prevention services, only 59% of FSW had received HIV testing before childbirth during their last pregnancy, and 30% of HIV-infected FSW had lost ≥1 children. Conclusions: Low contraceptive use and high burden of unintended pregnancy result in poor reproductive outcomes for FSW and avoidable mother-to-child HIV transmission risks. Integration of family planning and antenatal services into HIV prevention and care programs accessed by FSW could enhance reproductive outcomes and HIV prevention goals.